Modeling the modulus of bitumen/SBS composite at different temperatures based on kinetic models. (8th February 2022) - Yan, Chuanqi; Lv, Quan; Zhang, Allen A.; Ai, Changfa; Huang, Weidong; Ren, Dongya
Abstract: Bitumen/styrene-butadiene-styrene (SBS) polymer composite material (also coded as polymer modified bitumen, PMB) is one of the most employed composite materials in the pavement industry. PMB is viscoelastic and exhibits temperature-dependent modulus. Abundant researches have investigated the influence of temperature on the PMB modulus, however few have attempted to establish a model to describe the direct relationship between the PMB modulus and the temperature. This paper aims to use a kinetic model for fiber reinforced composite to describe the inherent relationship between the PMB modulus and temperature. Furthermore, a modified model is proposed to find better fitting results specifically for PMB composite. Considering the fact that PMB has a much higher polydispersity, the modified model uses nonlinear least squares regression instead of the original Coats–Redfern method to determine the kinetic parameters (activation energy and pre-exponential factor). The determination of glassy state modulus and rubbery state modulus is also replaced by numerical optimization instead of visual inspection. The predicted modulus was compared with experimental results obtained by Dynamic Mechanical Analysis (DMA), and a good agreement was found. The method introduced by this study could be a promising approach to study the temperature-dependent properties and state transition behaviors of PMB composite. Graphical abstract: Image 1